Implementation of the Wordwall Platform as an Effort to Improve Students' Mathematics Learning Achievement in Elementary School - Kadek Lilik Dwi Cahyaningsih; I Putu Suardipa; I Komang Wahyu Wiguna (Lembaga Bale Literasi, 2026)
This study aims to delineate the efficacy of employing the Wordwall application to optimize Mathematics learning outcomes for fourth-grade students at SD Negeri 5 Karangasem. The fundamental problem precipitating this research was the low fulfillment of learning mastery criteria due to the dominance of one-way teaching and the minimal use of interactive media, making Mathematics perceived as difficult by students. This study adopted a Classroom Action Research (CAR) design with a descriptive quantitative approach, executed across two cycles (comprising planning, action, observation, and reflection phases). The subjects involved 28 fourth-grade students. Data collection was conducted through cognitive tests, activity observation sheets, and documentation. Empirical findings indicate that utilizing Wordwall significantly boosted students' academic achievements. During the pre-cycle phase, the class average was only 55 with a classical mastery rate of 35.7%. Following the intervention in Cycle I, the average score climbed to 70 with a passing rate of 65%. In Cycle II, a sharper escalation occurred, with the average score hitting 85 and the classical mastery rate reaching 89%. Beyond cognitive improvements, field observations demonstrated increased motivation and active student participation, driven by interactive gamification elements such as quizzes, matching games, and random wheels. In conclusion, the Wordwall application is highly effective in elevating elementary students' Mathematics scores. This study recommends that educators integrate digital game-based media to construct dynamic and interactive learning environments while supporting digital acceleration in primary education.